Progress in Production of 1, 3-propanediol From Selective Hydrogenolysis of Glycerol - Chen, Jinghu; Xia, Qineng; Wang, Yangang; Huang, Yuandong (Frontiers in Chemical Engineering, 2020)
1,3-propanediol (1,3-PDO) is an important bulk chemical widely used in the polyester and polyurethane industry. The selective hydrogenolysis of glycerol to value-added 1,3-PDO is extremely attractive. However, the formation of 1,3-PDO is less thermodynamically stable than 1,2-PDO, and the steric hindrance effect in the reaction process makes the highly selective production of 1,3-PDO a great challenge. In this mini review, the recent research progress on the selective catalytic hydrogenolysis of glycerol to 1,3-PDO is overviewed and the catalytic mechanism of the reaction is summarized. We mainly focus on the different performances of each type of catalyst (Pt-W-based catalysts, Ir-Re based-catalysts, and other types) as well as the interactions between metals and supports. Finally, several personal perspectives on the opportunities and challenges within this promising field are discussed.